Struktur Kalimat Tunggal Bahasa Kanum Sota: The Structure of the Simple Sentence of Kanum Sota Language - Sitti Mariati S. (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2021)
Kanum Sota language is spoken by speaker aroun Sota District, Merauke, Papua Province. This study uses descriptive method to describe the structure of the simple sentence of Kanum Sota language. The result of analysis of the function of simple sentence elements shows us that the structures of simple sentence of Kanum Sota are Subject + Predicate (S+P), Subject + Object + Predicate (S + O + P), Subject + Predicate + Object (S + P + O), Subject + Adverb + Predicate (S + Adv. + P), and Subject + Obejct + Predicate + Adverb (S + O + P + Adv.). By simple sentence pattern, structure and kind of simple sentence of the Kanum Sota is known as follows: (1) transitive sentence whose pattern S:n/pron./NP + O:n/pron./NP + P: trans.Verb, and S:n/pron/NP + P:trans.verb + O:n/pron/NP, (2) Intransitive sentence pattern, S:n/pron/NP + P: intrans.verb, (3) descriptive sentence, S:n/pron/NP + P: adj./adj.phrase, (4) postposition sentence, S:n/pron/NP + P:postpositional phrase, (5) possessive sentence S:n/NP + P:possessive, (6) equative sentence S:n/pron/NP + P:n, and (7) numeral sentence S:n/pron/NP + P:num.